Community Organization Approaches to the Prevention of Juvenile Delinquency - Berger, Cherylynne E. (1985)
This paper examines juvenile delinquency prevention programs which implement large-scale intervention and social change strategies. A typology of community organization practice is used to analyze the assumptions, objectives, and methods underlying these approaches. Three models of community organization-- locality development, social planning, and social action--are used to evaluate three exemplary delinquency prevention programs: the Chicago Area Project, the 1960's provision of opportunity programs, and the 1960's comprehensive community-based projects such as Mobilization for Youth. The difficulties encountered in implementing these models and programs are identified and assessed. The implications for contemporary crime prevention efforts are also considered